Application of measures for reduction of magnetic flux density levels in the apartment located above the 10/0.4 kV transformer station - Grbić, Maja; Pavlović, Aleksandar; Hrvić, Dejan (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
The paper analyzes the levels of magnetic flux density in the apartment located above the 10/0.4 kV distribution transformer station. During the first magnetic field testing, it was concluded that in the case of the rated load of the transformers, increased values of magnetic flux density would occur in the apartment. The main sources of magnetic field in the apartment were the busbars and cable lines connecting the transformers and the 0.4 kV distribution cabinets. For that reason it is proposed to apply measures to reduce the levels of magnetic flux density, which are described in detail in the paper. After implementing the proposed measures, magnetic field testing in the apartment was repeated. The paper presents magnetic field testing results before and after the application of the measures and gives a conclusion regarding the effectiveness of the applied measures as well as regarding the compliance of the levels of magnetic flux density with the exposure limit prescribed by the current national regulations.
Keywords: transformer station, magnetic field, non-ionizing radiation, electromagnetic field, area of increased sensitivity.